Associations of fear of hypoglycemia with second‐line use of insulin secretagogues or insulin and subsequent glycemic control in patients with type 2 diabetes: An analysis using data from the DISCOVER study. Issue 6 (11th February 2020) - Wang, Jun‐Sing; Chen, Hungta; Tang, Fengming; Sheu, Wayne Huey‐Herng
Abstract: Background: Associations of fear of hypoglycemia with prescription of second‐line insulin secretagogues (IS) or insulin and subsequent glycemic control in patients with type 2 diabetes were analysed using data from the DISCOVER study‐a large, prospective, observational study. Methods: Patients with type 2 diabetes initiating a second‐line treatment after a first‐line oral therapy were enrolled. Fear of hypoglycemia was assessed using baseline Hypoglycemia Fear Survey (HFS) worry score. Glycemic control was assessed using glycated haemoglobin (HbA1c) levels at 6‐month and 1‐year follow‐up, and HbA1c change from baseline was analysed. To examine the association of baseline HFS worry scores with second‐line use of IS or insulin, a hierarchical logistic model with country as random effect was used. Results: A total of 6217 patients were analysed. The mean HFS worry score was 6.9 ± 11.4, while patients in the upper quartile had an HFS worry score ≥9. We divided patients into three groups according to their baseline HFS worry score (0, 1‐8, ≥9). HFS worry score was associated with the use of first‐line IS, but not the second‐line treatment. Compared to treatments with no IS and insulin, a better HbA1c response to second‐line IS or insulin was noted in patients with a baseline HFS worry score of 0 or 1‐8, but not in patients with a baseline HFS worry score ≥9. Conclusion: HFS worry score was associated with the use of first‐line IS and glycemic response to second‐line IS or insulin in patients with type 2 diabetes. Trial registration: ClinicalTrials.gov NCT02322762. Registered 23 December 2014.